Optimization of scaffold for a successful hydrogel-seeding method for vascular tissue engineering - Park, In Su; Kim, Soo Hyun; Kim, Sang-Heon; Han, Jeong Woo; Chung Eunna; KO YOUNG-GUN
Porosity and pore size are needed for successful cell seeding and proliferation into porous scaffolds. This study was focused on a hydrogel-seeding method to improve cell adhesion and proliferation in tubular porous scaffolds for vascular grafts application. Tubular scaffolds were fabricated from a biodegradable elastic polymer, poly(L-lactide-co-ε-caprolactone) (PLCL) (50:50, Mn 1.58×105), by an extrusion-particulate leaching method. Vascular smooth muscle cells (VSMCs) were dispersed in collagen hydrogel and then seeded into the tubular PLCL scaffolds having various pore sizes, 50-100 ？m, 100-200 ？m, and 300-500 ？m, respectively. As a result, the efficiency of cell adhesion and proliferation was dependent on the pore size of the scaffolds. Especially, the cell proliferation efficiency was improved by using the hydrogel-seeding method as compared with by using a previously established method. In summary, this study demonstrates that the efficiency of cell adhesion and proliferation was dependent on the pore size of the scaffolds in the hydrogel-seeding method.
Keywords: hydrogel; collagen; smooth muscle cells; vascular tissue engineering; pore size